Significant association between systemic inflammation response index and prognosis in patients with urological malignancies - Ma, Wangbin; Liu, Rongqiang; Li, Xinyi; Yu, Jia; Wang, Weixing (Frontiers in Immunology, 2025)
BackgroundThe systemic inflammation response index (SIRI) as an immune marker, is associated with prognosis of urological malignancies(UM). However, the conclusion remains controversial. Therefore, the objective of this study was to conduct a meta-analysis to comprehensively evaluate the predictive value of SIRI in patients with UM.MethodsA comprehensive search of PubMed, Web of Science, and EMBASE databases was performed for articles investigating the association between SIRI and UM. The search deadline was August 28, 2024. Survival outcome such as overall survival (OS), disease-free survival (DFS), progression-free survival (PFS), and recurrence-free survival (RFS) were analyzed.Results15 studies from 13 articles involving 4985 patients were included in the meta-analysis. The results showed that increased SIRI was associated with poorer OS (HR: 2.16, 95% CI: 1.61-2.89) and DFS/PFS/RFS (HR: 3.56, 95% CI: 1.41-8.99). Subgroup analysis further confirmed the prognostic value of SIRI in urinary system cancer.